Amacrine cells coupled to ganglion cells via gap junctions are highly vulnerable in glaucomatous mouse retinas. Issue 1 (25th July 2016) - Akopian, Abram; Kumar, Sandeep; Ramakrishnan, Hariharasubramanian; Viswanathan, Suresh; Bloomfield, Stewart A.
ABSTRACT: We determined whether the structural and functional integrity of amacrine cells (ACs), the largest cohort of neurons in the mammalian retina, are affected in glaucoma. Intraocular injection of microbeads was made in mouse eyes to elevate intraocular pressure as a model of experimental glaucoma. Specific immunocytochemical markers were used to identify AC and displaced (d)ACs subpopulations in both the inner nuclear and ganglion cell layers, respectively, and to distinguish them from retinal ganglion cells (RGCs). Calretinin‐ and γ‐aminobutyric acid (GABA)‐immunoreactive (IR) cells were highly vulnerable to glaucomatous damage, whereas choline acetyltransferase (ChAT)‐positive and glycinergic AC subtypes were unaffected. The AC loss began 4 weeks after initial microbead injection, corresponding to the time course of RGC loss. Recordings of electroretinogram (ERG) oscillatory potentials and scotopic threshold responses, which reflect AC and RGC activity, were significantly attenuated in glaucomatous eyes following a time course that matched that of the AC and RGC loss. Moreover, we found that it was the ACs coupled to RGCs via gap junctions that were lost in glaucoma, whereas uncoupled ACs were largely unaffected. Our results suggest that AC loss in glaucoma occurs secondary to RGC death through the gap junction–mediated bystander effect. J. Comp. Neurol. 527:159–173, 2019. © 2016 Wiley Periodicals, Inc. Abstract : In this study we show that the structural and functional integrity of retinal amacrine cells are compromised in a mouse model of glaucoma. Specific immunocytochemical markers were used to identify amacrine cell subpopulations in both the inner nuclear and ganglion cell layers. Calretinin‐ and GABA‐ immunoreactive cells were highly vulnerable to glaucomatous damage, whereas ChAT‐positive and glycinergic amacrine cell subtypes were largely unaffected. This difference between amacrine cell subtypes appears to be related to their gap junctional coupling patterns. Amacrine cells that are coupled to ganglion cells were lost in glaucoma, whereas uncoupled amacrine cells were not. Our results suggest that amacrine cell loss in glaucoma occurs secondary to ganglion cell death through the gap junction–mediated bystander effect.